Video transcoding for H.264 in the compressed domain and key techniques analysis - YANG Gao-bo1; YU Sheng-fa2; ZHANG Zhao-yang3 (Tongxin xuebao)
Based on the analysis of the difference between the newest video coding standard H.264 and the earlier video-coding standard,the advances in the key technologies for H.264 video transcoding,which was directly conducted in the compressed domain,were systematically discussed.They were classified into four categories: DCT-to-HT coeffi-cients conversion,fast motion re-estimation and refinement,inter/intra coding mode decision and rate control.Future di-rections on this topic were also prospected.